Pertumbuhan dan Hasil Empat Genotipe Padi (Oryiza Satifa L.) pada Sistem Budidaya Integrasi Padi-Ikan Secara Aquaponik - Suparmin, Muhammad Miftahurohman; Rahmadi, Rizky; Dulbari, Dulbari; Subarjo, Subarjo (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Alternatives to increase rice production are urgent to meet national food needs and the decline in agricultural land area. This study aims to determine the growth and yield of several rice genotypes in the rice-fish integration cultivation system. The research was arranged using 2 divided blocks, the first block without additional NPK fertilizer and the second block with additional NPK fertilizer. Using 4 genotypes and 5 replicates. The results showed that the genotype Inpari Nutri Zinc with additional NPK produced the highest plant height and number of filled grains. The integration of aquaponic rice-fish cultivation system with the addition of NPK fertilizer has been proven to increase the weight of filled grain per panicle by 26.4% and the weight of 1000 grains by 33.5% in Genotype PTP 01.